Financial exploitation perpetrated by family members in Malaysia: a socio-legal analysis - Kahar, Rojanah; Hasbullah @ Abdullah, Muslihah; Che Amani, Nurfadhilah (Universiti Islam Melaka, 2024)
In the absence of specific legislation addressing elder abuse or exploitation, the prevalence of financial exploitation incidents among older people in Malaysia is the second highest after psychological abuse. This qualitative study aimed to examine the legal protection for financial exploitation and explore the perception of older people about their experience of financial exploitation perpetrated by family members; the barriers they faced in disclosing and seeking help, and the ways they dealt with financial exploitation. Thorough thematic analysis, six major themes were identified to describe the experience of participants with financial exploitation by family members. The first theme elucidates the concept of ‘harm, which implies violation of rights, financial insufficiency and indirect harm. The second theme is ‘exploit, which discusses attachment bond, vulnerability and family expectation. The study also discovered how participants felt ‘family comes first’ and ‘helplessness’ as main barriers that hinders them from disclosing the incidents to others. This study also explored various ways on how participants responded to their financial exploitation experiences by ‘seeking assistance’ and ‘non-seeking assistance. Participants in the study chose spiritual healing as a means of coping with the situation and wished for solutions that did not involve authorities in resolving this issue. The participants expressed a clear desire for action to be taken to prevent older Malaysians becoming victims of such acts and empower them. The findings demonstrate the critical nature of understanding the realities and barriers faced by victims of elder financial exploitation in Malaysia and how these experiences impact their quality of life. This finding also highlights the critical need to revisit existing policies and laws relating to financial exploitation of older people, to close the gap of underreporting and promote help-seeking behaviour among victims and society at large.